Basketball : a history of hoops - Stewart, Mark, 1960 July 7- (New York : F. Watts, 1998)
Discusses the origins and evolution of the sport of basketball, as well as important events and key personalities in both college and professional versions of the game.
Includes bibliographical references (p. 151) and index.
English Language & Literature.
Keywords: Basketball -- United States -- History -- Juvenile literature; Basketball -- History